A Quality Improvement Project on Pain Management at a Tertiary Pediatric Hospital. Issue 3 (September 2022) - Wilding, Jodi; Scott, Hailey; Suwalska, Victoria; Geddes, Zarina; Venegas, Carolina Lavin; Long, Deborah; Macartney, Gail; MacNeil, Mary; Martelli, Brenda; Mervitz, Deborah; Reszel, Jessica; Theoret-Douglas, Carol; et al.
: To assess and improve pain management practices for hospitalized children in an urban tertiary pediatric teaching hospital. Methods: Health Quality Ontario Quality Improvement (QI) framework informed this study. A pre (T1) – post (T2) intervention assessment included chart reviews and children/caregiver surveys to ascertain pain management practices. Information on self-reported pain intensity, painful procedures, pain treatment and satisfaction were obtained from children/caregivers. Documented pain assessment, pain scores, and pharmacological/non-pharmacological pain treatments were collected by chart review. T1 data was fed back to pediatric units to inform their decisions and pain management targets. Results: At T1, 51 (58% of eligible participants) children/caregivers participated. At T2, 86 (97%) chart reviews and 51 (54%) children/caregivers surveys were completed. Most children/caregivers at T1 (78%) and T2 (80%) reported moderate to severe pain during their hospitalization. A mean of 2.6 painful procedures were documented in the previous 24 h, with the most common being needle-related procedures at both T1 and T2. Pain management strategies were infrequently used during needle-related procedures at both time points. Conclusion: No improvements in pain management as measured by the T1 and T2 data occurred. Findings informed further pain management initiatives in the participating hospital.